2017
DOI: 10.1186/s12888-017-1404-1
|View full text |Cite
|
Sign up to set email alerts
|

Minor depression in older, long-term unemployed people seeking vocational support

Abstract: BackgroundPrevalence rates of minor and major depression vary from 0.7 to 6.8 (minor) and 3.8 to 10.9 (major) for the general population. Twenty-two percent of older, long-term unemployed people suffer from major depression. However, the prevalence rate of minor depression (depression on a subthreshold level with less than 5, but more than 1 depression symptom) in this population is unknown. The first aim of this study is to identify that prevalence rate, because we already know that minor depression increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In Table 3, the absolute values of regression coefficients of those who work, participate in social activities, and do regular physical activities are all smaller than the opposite. Numerous studies concerning this issue are consistent with the results [29][30][31][32][33][34]. Third, those with a greater number of chronic medical conditions experience more severe cognitive impairment accompanied with change in depressive state.…”
Section: Discussionsupporting
confidence: 71%
“…In Table 3, the absolute values of regression coefficients of those who work, participate in social activities, and do regular physical activities are all smaller than the opposite. Numerous studies concerning this issue are consistent with the results [29][30][31][32][33][34]. Third, those with a greater number of chronic medical conditions experience more severe cognitive impairment accompanied with change in depressive state.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to living alone before moving into nursing homes, the current study also found that residents who had never been employed had a 2.911‐fold higher risk of having depressive symptoms than those who had been employed before. A recent study revealed that 50% of older, long‐term unemployed adults (50 years or older) had minor or major depression (Pfeil, Holtz, Kopf, Hegerl, & Rummel‐Kluge, ). In a meta‐analysis study, Paul and Moser () also concluded that unemployment was associated with mental health, including depression.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen of the 21 articles were published in the past 5 years. More than half (60%) were cross-sectional studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , while two were longitudinal prospective cohort studies 41,42 . Two articles used both cross-sectional and longitudinal study designs 1,24,40,43 .…”
Section: Characteristics Of the Selected Articlesmentioning
confidence: 99%
“…Two studies collected data via online assessments 32,38 , and four studies either retrospectively analyzed data or utilized previously collected datasets 29,31,39,47 . Two studies utilized healthy controls 30,45 , and six studies used the control groups or placebo groups for comparison [24][25][26]33,46,47 . The DSM-IV and DSM-V criteria were used the most by the reviewed articles to define fatigue 27,33,38,42 .…”
Section: Characteristics Of the Selected Articlesmentioning
confidence: 99%
See 1 more Smart Citation